IMPLEMENTASI TEKNOLOGI COMPUTER VISION SEBAGAI PENGENDALI MOBILE ROBOT BERBASIS KAMERA WEB - Samsul Arifin; Erwien Tjipta Wijaya (Universitas Islam Lamongan, 2017)
In this research will be developed autonomous Mobile Robot navigation system, using vision sensor in the form of web camera. The ability of the robot to find the path, avoiding obstacles in an indoor environment becomes the key to the success of navigation. One of the things that underlies the robot navigation system is the process of image information processing from a web camera. So it takes a method that can process image information from the web camera into image data more easily read by the computer. The method that can be used to solve this problem is Canny Edge Detection. Canny Edge Detection has some of the most optimum edge detection criteria that localize the image well, detect objects well and clear response. With these advantages, the Canny Edge Detection method can produce a more representative image approaching the real object. After the edge detection process is completed then the next step is to identify and identify paths or obstacles that exist. Paths and obstructions that have been identified will be used as models to determine which direction the robot will run. The whole process of computing and control will be done using Raspberry pi, while for image processing using OpenCV application.